Tackling the threats of Internet worms - Pathan, Al-Sakib Khan (IJIDCS Press, Bangladesh, 2012)
Computer Worm is a kind of malicious program that self-replicates automatically within a computer network. Again, Internet is defined as a network of networks. This is the reason why computer worms do not reside only within one computer or a single network but rather get spread all over the Internet whenever it is possible during computer-to-computer communications. The reality of today’s Internet is that the worms pose a major threat to the Internet infrastructure security. This is also understood that destruction of worms is not an easy task either and often very expensive. Multiple network devices and preventive mechanisms should be in place to hold appropriate defense at each step the communications are done through.